Opportunity and Challenges to Integrate Zakat Into Indonesian Fiscal System in The Light of Siyasah Shariyyah - Nashr Akbar; Saim Kayadibi (Faculty of Islamic Economics and Business, State Islamic University Sunan Kalijaga, 2013)
Nowadays, the idea of integrating zakat into fiscal system has arisen in Muslim countries including Indonesia. It is argued that zakat, in history, has played a significant role to create welfare among societies. It is proven at the time of Caliph 'Umar ibn 'Abdul 'Aziz that zakat has alleviated poverty at that time alongside tax. Having considered such achievement, some scholars argued that zakat should be reintegrated into current fiscal system. This paper, therefore, attempts to study the feasibility of integrating zakat into Indonesian fiscal system. Employing descriptive analysis based on Siyasah Shariyyah (high objectives of the Shariah). Therefore, the objectives of the study are set with these following points: 1) to address the strength and the weakness of the implementation of this idea, 2) to assess its opportunity as well as its threat, 3) to examine whether the integration of zakat will secure maslahah (benefit) or create mafsadah (harm). The result shows that the integration of zakat into current fiscal system is in line with the Siyasah Shariyyah. Hence, the strong willingness and commitment of government is strongly required to applicate it. The proper model of integration should also be planned well. Moreover, nurturing the understanding to all parties, especially to the nonMuslims and secularists, that this idea is really beneficial and not discriminatory should be promoted.